Searching for Cedar: Geographic Variation in Single Aeroallergen Shows Dose Response in Internet Search Activity. (2nd September 2015) - Willson, Thomas J.; Shams, Alexandra; Lospinoso, Joshua; Weitzel, Erik; McMains, Kevin
Abstract : Objective: To assess the effect of a single aeroallergen on Internet search activity in 3 distinct geographic regions over time. Study Design: A retrospective time series analysis. Setting: Tertiary academic medical center. Methods: Mountain Cedar pollen counts spanning the periods from 2011 to 2014 were collected for San Antonio, Dallas–Ft Worth, and Houston metro regions (Texas). Google search data for the corresponding period and regions were also obtained for the search terms pollen and mountain cedar. Data were analyzed through time series plots and autoregressive integrated moving average. Results: Seasonal maximum pollen counts were greatest in San Antonio, ranging from 5413 to 9982 grains per cubic centimeter. In San Antonio, there was a strong, positive, and statistically significant effect of mountain cedar pollen count on search activity for both pollen ( P =. 001) and mountain cedar ( P <. 001) when evaluated by autoregressive integrated moving average. Conclusions: Environmental levels of a single allergen—mountain cedar pollen—show a geographic and temporal relationship between Internet searches and mountain cedar pollen, based on Google Trends. These data are useful to understand patients' perceptions of the health risk presented by mountain cedar pollen. In turn, this information affords practitioners the opportunity to offer targeted patient education in a geographically unique region, as well as adjust surveillance of related pathologies.